Pengembangan Alat Evaluasi Pembelajaran Berbasis Android Melalui Aplikasi Quizziz pada Materi Puisi Siswa Kelas X SMA Nurul Amaliyah Tanjung Morawa - Rahma Yani (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2021)
This research aimed to describe the development process, practicality, validity, and feasibility of using an android-based learning evaluation tool through the quizizz application on "Poetry" material in class X SMA. This research was conducted in SMA Nurul Amaliyah Tanjung Morawa. The research used Research and Development method (R&D) with a 4D model developed by Thiagarajan which includes 4 stages, including: Definition, Design, Development, and Dissemination with a population of 83 students. Sampling in this study used a random sampling technique through lottery, so that there were 28 students used as samples. The data in this study include qualitative and quantitative data. The qualitative was obtained through interviews and comments and suggestions given by validators, while quantitative data was obtained through data collection in the form of distributing questionnaires to validation of material experts, media/design, teachers and student response, totaling 28 students in using learning evaluation tools based on android through the quizzz application.The results obtained are (1) an explanation of the process of developing learning evaluation tools through the resulting product in the form of a guidebook for the using of evaluation tools, (2) based on the validity test of the using of evaluation tools through material validators and media/design experts, obtained total values as 85.29% with "valid" qualifications, and the overall value of media/design expert validation as 90.15% with "very valid" qualifications, (3) based on the feasibility test of using evaluation tools conducted by two teachers of Bahasa Indonesia obtained an overall score as 91.2% with a “very decent” qualification, (4) while the practicality test of the evaluation tool through the assessment of the student response questionnaire obtained as 87.16% with "very practical" qualifications with various positive responses given by students. It can be concluded that the android-based learning evaluation tool through the Quizzzz application is very practical and suitable to be used.